The evolution of femoral morphology in giant non-avian theropod dinosaurs - Pintore, Romain; Hutchinson, John R.; Bishop, Peter J.; Tsai, Henry P.; Houssaye, Alexandra (Paleobiology, 2024)
Theropods are obligate bipedal dinosaurs that appeared 230 Ma and are still extant as birds. Their history is characterized by extreme variations in body mass, with gigantism evolving convergently between many lineages. However, no quantification of hindlimb functional morphology has shown whether these body mass increases led to similar specializations between distinct lineages. Here we studied femoral shape variation across 41 species of theropods (n = 68 specimens) using a high-density 3D geometric morphometric approach. We demonstrated that the heaviest theropods evolved wider epiphyses and a more distally located fourth trochanter, as previously demonstrated in early archosaurs, along with an upturned femoral head and a mediodistal crest that extended proximally along the shaft. Phylogenetically informed analyses highlighted that these traits evolved convergently within six major theropod lineages, regardless of their maximum body mass. Conversely, the most gracile femora were distinct from the rest of the dataset, which we interpret as a femoral specialization to “miniaturization” evolving close to Avialae (bird lineage). Our results support a gradual evolution of known “avian” features, such as the fusion between lesser and greater trochanters and a reduction of the epiphyseal offset, independent from body mass variations, which may relate to a more “avian” type of locomotion (more knee than hip driven). The distinction between body mass variations and a more “avian” locomotion is represented by a decoupling in the mediodistal crest morphology, whose biomechanical nature should be studied to better understand the importance of its functional role in gigantism, miniaturization, and higher parasagittal abilities.
Keywords: dept.bio; open-access; peer-reviewed

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Conner, L.M.; Goedert, D.; Fitzpatrick, S.W.; Fearnley, A.; Gallagher, E.L.; Peterman, J.D.; Forgione, M.E.; Kokosinska, S.; Hamilton, M.; Masala, L.A.; Merola, N.; Rico, H.; et al. (Chemosphere, 2024)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors associated with anthropogenic activities that affect many organisms across the planet – elevated salinity (e.g., from road de-icing salt) and temperature (e.g. from climate change). We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to pollution from road salt. When experimentally exposed to road salt, wood frogs showed reduced survival (especially those from ponds adjacent to roads), divergent developmental rates, and reduced longevity. Family-level effects mediated these outcomes, but high salinity generally eroded family-level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches. © 2024 Elsevier Ltd
Keywords: Amphibians; Climate change; Local adaptation; Maladaptation; Pollution; Road salt; dept.bio; peer-reviewed